Opioid use and opioid use disorder in mono and dual-system users of veteran affairs medical centers - Goulet, Joseph; Cheng, Yan; Becker, William; Brandt, Cynthia; Sandbrink, Friedhelm; Workman, Terri Elizabeth; Ma, Phillip; Libin, Alexander; Shara, Nawar; Spevak, Christopher; Kupersmith, Joel; Zeng-Treitler, Qing (Frontiers in Public Health, 2023)
Introduction: Efforts to achieve opioid guideline concordant care may be undermined when patients access multiple opioid prescription sources. Limited data are available on the impact of dual sources of care on receipt of opioid medications. Objective: We examined whether dual use was associated with increased rates of new opioid prescriptions, continued opioid prescriptions and diagnoses of opioid use disorder. We hypothesized that dual use would be associated with increased odds for each outcome. Methods: This retrospective cohort study was conducted using Veterans Administration (VA) data from two facilities from 2015 to 2019, and included active patients, defined as Veterans who had at least one encounter in a calendar year (2015-2019). Dual use was defined as receipt of VA care and VA payment for community care (non-VA) services. Mono users were defined as those who only received VA services. There were 77,225 dual and 442,824 mono users. Outcomes were three binary measures: new opioid prescription, continued opioid prescription (i.e., received an additional opioid prescription), and opioid use disorder diagnosis (during the calendar year). We conducted a multivariate logistic regression accounting for the repeated observations on patient and intra-class correlations within patients. Results: Dual users were significantly younger than mono users, more likely to be women, and less likely to report white race. In adjusted models, dual users were significantly more likely to receive a new opioid prescription during the observation period (Odds ratio (OR)=1.85, 95% confidence interval (CI) 1.76-1.93), continue prescriptions (OR=1.24, CI 1.22-1.27), and to receive an opioid use disorder diagnosis (OR=1.20, CI 1.14-1.27). Discussion: The prevalence of opioid prescriptions has been declining in US healthcare systems including VA, yet the prevalence of opioid misuse disorder has not been declining at the same rate. One potential problem is that detailed notes from non-VA visits are not immediately available to VA clinicians, and information about VA care is not readily available to non-VA sources. One implication of our findings is that better health system coordination is needed. Although care was paid for by the VA and presumably closely monitored, dual users were more likely to have new and continued opioid prescriptions.